2016
DOI: 10.1111/ijfs.13232
|View full text |Cite
|
Sign up to set email alerts
|

Green method for determination of phenolic compounds in mung bean (Vigna radiata L.) based on near‐infrared spectroscopy and chemometrics

Abstract: Summary Mung bean grains exhibit high level of antioxidant activity due the presence of phenolic compounds. Near‐infrared spectroscopy (NIRS), in conjunction with chemometrics, was used to develop a rapid, nondestructive, chemical free and easy‐to‐use method to determine these compounds in sixty genotypes of mung bean. NIRS calibration curve with high‐performance liquid chromatography (HPLC) as reference method was used to determine phenolic compounds (catechin, chlorogenic acid, caffeic acid, p‐coumaric acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Coincidentally, a previous study reported that isoflavones accumulate predominantly in plants of the Leguminosae family [33]. The concentrations of daidzein, glycitin and gallic acid determined in our study were similar to values reported previously in mung beans, but other major phenolics (vitexin, isovitexin, catechin, caffeic acid and ferulic acid) reported in mung beans were not detected in our study [34].…”
Section: Resultssupporting
confidence: 86%
“…Coincidentally, a previous study reported that isoflavones accumulate predominantly in plants of the Leguminosae family [33]. The concentrations of daidzein, glycitin and gallic acid determined in our study were similar to values reported previously in mung beans, but other major phenolics (vitexin, isovitexin, catechin, caffeic acid and ferulic acid) reported in mung beans were not detected in our study [34].…”
Section: Resultssupporting
confidence: 86%
“…These samples have also presented high antioxidant activities as assessed by DPPH, FRAP, and ABTS assay. It has been well reported in the literature that phenolic compounds prevent cardiovascular diseases, cataract development, oxidative injury caused by heat stress, lower the incidence of influenza infection, reduce fat absorption, and enhance energy expenditure [9,19]. Overall, significant differences (p < 0.05) were observed among the phenolic profiles and antioxidant activities of all chestnut samples procured from five different geographic regions of China.…”
Section: Phenolic and Antioxidant Properties Among 21 Raw Chestnut Samentioning
confidence: 76%
“…The legumes are reported to exhibit protective and therapeutic effects [2] as well as health benefits associated with the prevention of chronic diseases [3] such as breast cancer, cardiovascular diseases and cataract development. These health benefits are attributed to the high content of antioxidants present in the food legumes [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that the antioxidants from plants and plant-based foods are responsible for the reduction of radical-related pathogenicity [5]. Legumes are also reported to exhibit strong antioxidant capacities due to the presence of a wide range of various types of phenolic compounds [3,4]. Phenolic compounds are the small molecules characterized by having at least one phenol group in their structure.…”
Section: Introductionmentioning
confidence: 99%